2020
DOI: 10.1108/ejtd-08-2019-0141
|View full text |Cite
|
Sign up to set email alerts
|

Beyond supervisors’ support: influencing (international) technical training transfer

Abstract: Purpose This paper aims to provide an understanding of influencing motivation and volition in the transfer of learning within the context of technical training in different countries by controlling predictors. Design/methodology/approach In six countries, employees from one automotive company’s service centres were asked to complete two online questionnaires after a blended learning training program with technical content (t1: 7 to 12 days after the training, t2: 5 to 7 weeks after). In total, 441 technical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 34 publications
5
20
0
1
Order By: Relevance
“…Prior OCM studies investigated role supervisor's support to training/OCM (de Oliveira et al, 2019;Rawashdeh and Tamimi, 2019;Richter and Kauffeld, 2020). We add to this literature by investigating the role of trust.…”
Section: Discussionmentioning
confidence: 99%
“…Prior OCM studies investigated role supervisor's support to training/OCM (de Oliveira et al, 2019;Rawashdeh and Tamimi, 2019;Richter and Kauffeld, 2020). We add to this literature by investigating the role of trust.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al (2009) argue that national culture could have an important effect on learning and transfer because its social nature is dependent on the cultural context (values, beliefs, and social norms). However, the limited amount of available published studies that investigated cross-cultural comparisons in important predictors of training transfer have yet to identify significant differences between national cultures (e.g., Richter & Kauffeld, 2020;Yaghi & Bates, 2020). Although these studies do not support the general assumption that national culture has a significant impact on training transfer, underlying mechanisms related to transfer may differ between national cultures (Yaghi & Bates, 2020).…”
Section: Limitationsmentioning
confidence: 98%
“…These forms include social support from colleagues and supervisors, high‐quality relationships, transformational leadership, autonomy, job control, participation in decision‐making, performance feedback, opportunities for learning and growth, financial rewards and career opportunities (e.g., Bakker & Demerouti, 2007, 2008; Christian et al, 2011; Fernet et al, 2015; Hakanen et al, 2006; Schaufeli et al, 2009). Among these resources, the positive effect of social support on training transfer has received the most supporting evidence, with studies showing that higher levels of social support have been associated with higher levels of training transfer (e.g., Blume et al, 2010; Burke & Hutchins, 2007; Richter & Kauffeld, 2020). Other forms of job resources were also found to be important predictors.…”
Section: Introductionmentioning
confidence: 99%
“…These assumptions were supported by several previous studies. For example, motivation to transfer was found to partially mediate the relationship between feedback and training transfer (Van den Bossche et al, 2010) and the relationship between peer support and training transfer (Richter & Kauffeld, 2020; Salamon et al, 2022). Other studies found that the transfer motivation fully mediates the relationship between peer support and transfer (Bhatti et al, 2013; Massenberg et al, 2015; Reinhold et al, 2018).…”
Section: Introductionmentioning
confidence: 99%